Effect of phototherapy on platelet count in neonates with unconjugated hyperbilirubinemia - Akash Y. Malekar; Nitin S. Mehkarkar; Vaibhav J. Pustake; Ashwini B. Kundalwal (International Journal of Contemporary Pediatrics, 2023)
Background: Hyperbilirubinemia in newborn is quite common. Phototherapy (PT) is one of the most common noninvasive methods for the treatment of this hyperbilirubinemia. There are limited studies available on effect of PT on platelet count with contrasting results. So, this study was conducted to determine the effect of phototherapy on platelet counts of hyperbilirubinemic neonates in tertiary care hospital. Methods: This was a hospital based prospective study on 60 eligible neonates admitted in neonatal intensive care unit (NICU) for neonatal hyperbilirubinemia and phototherapy during January 2021 to June 2022. Platelet count was done before starting phototherapy, 24 hours after phototherapy and before discontinuing phototherapy. The results were analyzed statistically using Chi square test and t-test. P value <0.05 was considered as statistically significant. Results: In this study, total of 60 neonates were included of which 33 were males and 27 were females. The mean (±SD) platelet counts were 201764.92±18 before phototherapy and 156578.33±38 after phototherapy. There was a significant decline in the mean platelet count 24 hours after phototherapy and before stopping phototherapy. (p<0.05). Conclusions: In our study, the mean platelet count was decreased significantly after phototherapy. Hence, unnecessary use and prolongation of phototherapy should be avoided.